A Guidance to Systematic Literature Review to Young Researchers by Telkom University and the University of Turin - Mahir Pradana; Anita Silvianita; Putu Nina Madiawati; Davide Calandra; Federico Lanzalonga; Michele Oppioli (Universitas Andi Djemma, 2023)
The purpose of a systematic literature review is to provide a clear and objective summary of the current state of knowledge on a particular topic, identify gaps in the literature, and suggest areas for future research. This type of review is widely used in many fields, including healthcare, education, psychology, and social sciences, to inform evidence-based decision-making, policy development, and practice guidelines. The process of conducting a systematic literature review requires careful planning, attention to detail, and a systematic approach to data collection and analysis. The resulting review is a valuable resource for researchers, practitioners, and policymakers seeking to understand the current state of knowledge in a given field. To introduce this method to young researchers in Indonesia, MBA Telkom University worked together with the department of management at the University of Turin (Italy) to have a 2-hours session about systematic literature review. This article is the summary of the event.Keywords: systematic literature review, bibliometric, research methodology, workshop